Morphological analysis of triangulated models of grinding wheels working surfaces - Grabchenko, A. I.; Dobroskok, V. L.; Garashchenko, Ya. N.; Shpilka, A. N. (University of Miskolc, 2015)
Methods of obtaining and morphological analysis of a triangulated model of grinding wheels are described. The model is made from a set of photos of the investigated working surface of the wheels, which have a different spatial orientation of the depth field of image space while shooting.